A methodological framework for project-based collaborative learning in a networked environment. (1st January 2002) - Daradoumis, T.; Xhafa, F.; Marques, J.M.
In this work, we present a new way to use existing technology in a real learning context. We investigate and propose a scenario based on collaborative work of virtual groups of students developing a software project. Our intent is to promote learning through collaborative implementation of a project in shared workspaces. This raises several important issues that concern virtual group formation techniques, group regulation and role-playing by students. Other important aspects are related to the pedagogical side and include setting project development phases, assessment, tutor role, student tracking, and the tutor's understanding and awareness of the social and cognitive processes. We consider them to be fundamental concerns and influencing factors in supervising, guiding and enhancing the collaborative learning process. Our approach describes the bases of a methodological framework for collaborative project development and proposes some solutions to the above matters. It also allows for the exploration of new forms of collaborative learning and teaching.